(untitled) (Anclajes, 2021)
In this article I examine a specific aspect of the literary relation between Antonio José Ponte and Lorenzo García Vega by analyzing their respective essays on the work of Julián del Casal. In the first part, I consider the main arguments of García Vega’s well-known “La opereta cubana en Julián del Casal”. In the second, I clarify the continuities and differences that Ponte establishes in El libro perdido de los origenistas, and analyze its depictions of Martí and Casal. Finally, I reflect on García Vega and Ponte’s forms of enunciation.